From Executive Hubris to Identity Threats: A Systematic Review of M&A Failure - Dini Aurelia; Yusnaini Yusnaini (GLOBAL SCIENTS PUBLISHER, 2026)
Research investigates the critical nexus between leadership ethics and behavioral integrity within post-merger integration frameworks. Utilizing a systematic synthesis of 41 high-impact studies, the investigation examines how executive narcissism and identity dissonance catalyze systemic ethical risks. Analysis identifies a significant correlation between aggressive “Tone at the Top” and defensive mechanisms, including knowledge hiding and moral sabotage among professionals. Findings underscore that successful integration hinges upon stewardship-oriented governance rather than conventional financial synergies. Strategic alignment of corporate integrity remains the paramount prerequisite for safeguarding long-term organizational stability and institutional trust.